SISTEM PERBAIKAN EKOFISIOLOGI TANAMAN SENGON (Paraserianthes falcataria (L) Nielsen ) DI KECAMATAN WAGIR, 161 MALANG - Febri Arif Cahyo Wibowo; Rosa Septiana Mieske Putri; Amir Syarifuddin; Tatag Muttaqin (Lambung Mangkurat University-Indonesia, 2020)
Sengon plant (Paraserianthes falcataria (L) Nielsen) in Indonesia is one of the types of plants developed in the development of Community Forestry especially in Wagir District, Malang Regency. This study was conducted to analyze the effect of environmental conditions, especially temperature and humidity on stomata density and chlorophyll levels in the plant Sengon (Paraserianthes falcataria (L) Nielsen) and analyze the soil nutrient content under the Sengon stand (Paraserianthes falcataria (L) Nielsen) on plant physiology in Sukodadi Village, Wagir District, Malang Regency. The techniques used are field surveys, leaf sampling to measure physiological properties (stomata density and chlorophyll content), and soil sampling to measure soil chemical properties (macro nutrient content), as well as direct observations in the field to measure environmental factors (temperature and humidity). Analysis of the data used is multiple linear regression in SPSS to determine whether there is influence of temperature and humidity on the physiology of stomata and chlorophyll as well as descriptive analysis on soil factors. Research result is that temperature and humadity have an effect on chlorophyll. This support to possibility of temperature and humadity system in the region so that agreed crops will affect the concentration of chlorine.